Sistem Pengambilan Keputusan Bedah Rumah pada Dinas Perumahan Kawasan Pemukiman dan Pertanahan Menggunakan Metode Weight Product (WP) - Maichel Avenio Nahak; Gergorius Kopong Pati; Dian Fransiska Ledi (Modem : Jurnal Informatika dan Sains Teknologi., 2026)
The house renovation program is one of the government's efforts to improve the quality of housing for low-income people. However, the process of selecting recipients of home surgery assistance is often faced with obstacles in determining the right and fair priorities for recipients. Therefore, this study aims to design and implement a home surgery decision-making system at the Housing, Residential Areas, and Land Office using the Weight Product (WP) method. The WP method was chosen because of its ability to conduct an objective assessment of various relevant criteria, such as the condition of the house, ownership status, level of welfare, and socioeconomic needs of the recipient. This system will give weight to each criterion used to determine the priority of home surgical assistance for residents in need. In its implementation, this system is able to process data from various prospective recipients and produce an automatic and transparent order of priority recipients. The results of the evaluation show that this system can improve efficiency and accuracy in the decision-making process, as well as assist the Housing Office in implementing the house renovation program more on target. With this system, it is hoped that the home renovation program can provide greater benefits to people in need, as well as accelerate the implementation of better housing programs.